The importance of the western corn rootworm (Diabrotica virgifera virgifera LeConte) in Bavaria – local relevance and economic impact on single farms - Köhler, Katrin; Schätzl, Robert (Julius-Kühn-Archiv, 2014)
The western corn rootworm (Diabrotica virgifera virgifera LeConte), holding a quarantine status in the European Union, was first discovered in 2007 in southern Bavaria. In the course of Diabrotica Research Program of Germany and the states of Bavaria and Baden-Württemberg, an economic accompanying research is conducted at single farm level in Bavaria. This aims to evaluate different adaptation measures concerning the eradication and containment strategies economically. The focus of the analysis is mainly the crop rotation and the reduction of the proportion of maize at farm level. InVeKoS-data are analyzed, in order to assess the economic relevance of the pest in Bavaria in a better way. These enable detailed information on the development of maize production and cropping intensity. Subsequently research regions are defined with a high maize density, expecting enhanced damage from the beetle. In these selected areas single farms are selected. For considerations on single farm level, farms with different farm types are chosen by which adaptation measures are evaluated and realistic impact assessment could be made. For the evaluation of the economic impacts a whole-farm simulation has been used to include indirect effects of different adoption strategies. Additional, semi-structured interviews were conducted at selected farms in order to prove the results of the case study, obtain more information about the consequences on farm level and to evaluate the proposed cultivation alternatives for maize. A benefit-cost analysis and the comparative analysis of possible damage caused by the beetle and cost adjustments complete the study.